Effect of soil moisture status on seed quality of Bambara groundnut (Vigna subterranea L. Verde.) cultivars in Ghana - Laary, J.K.; Ofori, K.; Kumaga, F.K. (Asian Journal of Agricultural Research, 2012)
Studies were carried out in Ghana, to determine seed quality of Bambara groundnut, using two cultivars; Jabajaba (cream-seeded) and Chichele Balgu (red-seeded), under three soil moisture regimes of 30-40, 50-60 and >70%. Soil moisture significantly (LSD 5%) affected seed size, protein and tannin contents of Bambara groundnut. Tannin content was lower at >70% soil moisture than at 50-60% soil moisture but highest at 30-40% soil moisture. The 50-60% soil moisture favored good seed size and protein content than at 30-40 and >70% soil moisture regimes. The 30-40% soil moisture did not favor good quality seed development of Bambara groundnut cultivars. At each moisture regime, cream-seeded cultivar (Jabajaba) recorded lower seed sizes, higher protein and lower tannin contents than red-seeded cultivar (Chichele Balgu). Selecting cultivars with high protein and low tannin contents and growing them under optimum conditions that favor 50-60% soil moisture regime will improve seed quality of Bambara groundnut. © 2012 Knowledgia Review, Malaysia.
Keywords: Bambara groundnut; Protein; Seed size; Selection; Soil moisture; Tannins